2011
DOI: 10.1203/pdr.0b013e3182275164
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Values of Candidate Urine Acute Kidney Injury Biomarkers Vary by Gestational Age in Premature Infants

Abstract: Acute kidney injury (AKI) is common in premature infants and is associated with poor outcomes. Novel biomarkers can detect AKI promptly. Because premature infants are born with underdeveloped kidneys, baseline biomarker values may differ. We describe baseline values of urinary neutrophil gelatinase associated lipocalin, (NGAL), Interleukin - 18 (IL-18), Kidney Injury Molecule -1 (KIM -1), Osteopontin (OPN), beta-2 microglobulin (B2mG) and Cystatin-C (Cys-C). Next, we test the hypothesis that these biomarkers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
128
2
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(150 citation statements)
references
References 31 publications
16
128
2
4
Order By: Relevance
“…Chen et al (19) reported lower urine EGF levels in infants with severe perinatal asphyxia compared with controls, suggesting that EGF may play a role in the repair of acute renal injury after asphyxia. We controlled for birth weight as a potential confounder in evaluating the association between urine biomarkers and AKI to ensure that the detected changes in these biomarkers are not simply a reflection of prematurity (20). Askenazi et al (21) demonstrated that urinary biomarkers can predict AKI and mortality in very-low-birth-weight infants independent of gestational age and birth weight.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al (19) reported lower urine EGF levels in infants with severe perinatal asphyxia compared with controls, suggesting that EGF may play a role in the repair of acute renal injury after asphyxia. We controlled for birth weight as a potential confounder in evaluating the association between urine biomarkers and AKI to ensure that the detected changes in these biomarkers are not simply a reflection of prematurity (20). Askenazi et al (21) demonstrated that urinary biomarkers can predict AKI and mortality in very-low-birth-weight infants independent of gestational age and birth weight.…”
Section: Discussionmentioning
confidence: 99%
“…Another study has examined the role of gestational age within the urinary proteome looking at pre-selected markers. Urinary levels of neutrophil gelatinase-associated lipocalin, osteopontin, and beta-2 microglobulin decreased as the gestational age of the infant increased (26). Our study used a targeted approach to identifying markers of renal development and we have discovered a number of novel markers that may play a role in renal development or renal injury.…”
Section: Articlesmentioning
confidence: 94%
“…This study reveals marked differences in urinary cytokines between infants undergoing completion of nephrogenesis and those undergoing normal postnatal renal maturation. Gestational and postnatal age affect the urinary levels of many proteins and cytokines (26). Another study has examined the role of gestational age within the urinary proteome looking at pre-selected markers.…”
Section: Articlesmentioning
confidence: 99%
“…Recent studies have shown that immature neonates have higher concentrations of these biomarkers in the urine. This is probably due to the inability of the immature tubules to reabsorb proteins (6,30,31). There are very few studies that have examined these biomarkers in the neonates.…”
Section: Discussionmentioning
confidence: 99%